2013
DOI: 10.1016/j.jacc.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

One-Stop Hybrid Coronary Revascularization Versus Coronary Artery Bypass Grafting and Percutaneous Coronary Intervention for the Treatment of Multivessel Coronary Artery Disease

Abstract: One-stop HCR provides favorable midterm outcomes for selected patients with multivessel coronary artery disease in each risk tertile. For patients with high EuroSCORE or SYNTAX score, it might provide a promising alternative to CABG and PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 35 publications
3
69
1
4
Order By: Relevance
“…20 The reported stroke rates were 0% to 1.7%. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] It is notable that despite the anaortic approach used for the HCR CABG arm (mostly in situ LIMA conduit), the stroke rates are not much lower.There are two meta-analyses that evaluate the studies done on HCR and conventional CABG patients (Table 2). 27,28 Phan and Harskamp both showed that there is no benefit for perioperative mortality, stroke, or 1-year freedom from major adverse events when using HCR over CABG.…”
mentioning
confidence: 99%
“…20 The reported stroke rates were 0% to 1.7%. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] It is notable that despite the anaortic approach used for the HCR CABG arm (mostly in situ LIMA conduit), the stroke rates are not much lower.There are two meta-analyses that evaluate the studies done on HCR and conventional CABG patients (Table 2). 27,28 Phan and Harskamp both showed that there is no benefit for perioperative mortality, stroke, or 1-year freedom from major adverse events when using HCR over CABG.…”
mentioning
confidence: 99%
“…[1][2][3] In most cases, HCR involves a surgical procedure in which the internal mammary artery (IMA) is grafted to the left anterior descending (LAD) coronary artery, preceded or followed by percutaneous coronary intervention (PCI) of non-LAD coronary lesions, either performed in 1 setting (concurrent) or as a staged procedure. 4 A prerequisite for HCR is that the patient has LAD anatomy that is eligible for surgical revascularization, but also has non-LAD lesions that are amenable for PCI.…”
mentioning
confidence: 99%
“…Preliminary studies have shown that a hybrid approach compares favorably with both PCI and traditional CABG. 51,52 If an appropriately designed and powered randomized trial can demonstrate significant benefit with this approach over PCI alone and CABG alone, it may become a preferred approach for many patients and physicians.…”
Section: Will Cabg Utilization Stop Declining?mentioning
confidence: 99%